DEVELOPMENT OF AN E-MODULE BASED ON AUTHENTIC LEARNING IN THE CONTEXT OF WETLANDS FOR ARCHIMEDES’ PRINCIPLE MATERIAL - Lasiani, Lasiani; syahmani, syahmani; Salam, Abdul; Mahtari, Saiyidah; Setiono, Isnaini Agus (Universitas Negeri Padang, 2025)
Physics is often considered an abstract subject, posing challenges for students to fully comprehend its concepts. The integration of advancing technology as a learning medium can facilitate students’ understanding, particularly when combined with authentic learning approaches that present concrete situations. This allows students to observe, analyze, perform, and even experience concepts firsthand. An e-module based on authentic learning within the context of wetlands can serve as an effective learning medium. This study aims to develop a valid and practical e-module based on authentic learning in the context of wetlands for teaching Archimedes’ principle. The validity of the e-module was assessed through expert validation involving three specialists, while practicality and readability were evaluated using student response questionnaires. The research follows the Research and Development (R&D) methodology using the ADDIE model, which consists of five stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The study was conducted in the Physics Education program at Lambung Mangkurat University (ULM) in Banjarmasin. The validation results indicated that the material expert assessment achieved a score of 100%, the language expert assessment scored 93.75%, and the media expert assessment scored 91.67%, with an overall average validation score of 95.14%. The readability test yielded an average score of 91.38%, while student response assessments resulted in an average score of 93.89%. Based on these findings, it can be concluded that the developed e-module is highly feasible, valid, fully readable, and practical for use in learning.